Between Foreign Policy and Development Assistance: The UAE International Cooperation in Africa. Issue 2 (4th May 2022) - Guéraiche, William
Abstract : After 2013, the UAE multiplied the international aid tenfold to the African continent. From this year onwards, the aid has never dropped below $1 billion, three times the amount allocated prior to 2013. What are the main drivers of this change? This article postulates that three main factors triggered a heightened international aid in the African continent: economic considerations (trade and investments), security issues and a new approach to international cooperation. Official data allows the comparison of the evolution of the Emirati economic interests (mainly trade) with the aid. The statistics show that there are connections between trade and aid but no direct correlations. Over the last two decades, the nexus formed with economics, security and humanitarianism has become more visible. The best way to analyze the bilateral relations between the UAE and African states is probably to pay more attention to the depth of the relations rather than to the sectors that they cover.